Why Organizers Fail : The Story of a Rent Strike. - Brill, Harry (Berkeley : University of California Press, 2020)
This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1971.
Intro -- CONTENTS -- PREFACE -- 1 INTRODUCTION -- 2 RACE POLITICS IN THE GRANADA POVERTY PROGRAM -- 3 NAC AND THE TENANTS -- 4 NAC AND THE ESTABLISHMENT -- 5 NAC AND THE LAWYERS -- 6 CONCLUSION -- APPENDIX A LOOK AT MY FIELD EXPERIENCE
Description based upon print version of record.
JSTOR
Keywords: Community power -- United States -- Case studies; Poor -- United States -- Case studies; Rent strikes -- United States -- Case studies; Pouvoir communautaire -- États-Unis -- Études de cas; Grèves des loyers -- États-Unis -- Études de cas; Community power; Poor; Rent strikes; United States; Community power -- United States -- Case studies; Poor -- United States -- Case studies; Rent strikes -- United States -- Case studies; Case studies